Contribution to COVID-19 Gender and Social Protection Guidance Note of the Australian Government - CGIAR Research Program on Policies, Institutions, and Markets (2020)
This guidance note aims to support staff of the Australian Department of Foreign Affairs and Trade in implementing gender-sensitive social protection programming as part of a COVID-19 response program.